Assessment of the Extent of Compliance with the Curriculum and Instructional Materials in the Early Childhood Care and Education Centres in Anambra State - Caroline Dike, Ibiwari; Nneka Onwurah, Chimezie; Enuma Obiweluozor, Patience; Eugenia Uzodinma, Uchenna (International Journal of Psychosocial Rehabilitation, 2021)
This study sought to assess of the extent of compliance with the curriculum and instructional materials provisions and practices in the early childhood care and education (ECCE) centres in Anambra state. Evaluative research design was adopted in the study. A total of 60 ECCE centres in Anambra State were involved in the study. The instrument for data collection was a Kit on the Evaluation of the extent of compliance with the curriculum and instructional materials provisions and practices in the ECCE centres in Anambra state, with direct observation and unstructured interview. The instrument was validated by experts and experienced personnel and used to collect data. The internal consistency of the instrument was determined using Cronbach Alpha. The reliability estimate.76. Percentages, frequency count and mean statistics were used to answer the research questions, while chi-square and student t-statistics were used to test the null hypothesis. The major findings of the study were that: the private and public ECCE centres operate similar curriculum and instructional material provisions. Among the educational implications of the findings of the study was that well established and well managed ECCE services in both public and private centres could ensure uniformity in curriculum content and curriculum implementation